TINGKAT PARTISIPASI MASYARAKAT DALAM PELAKSANAAN PROGRAM MODEL DESA KONSERVASI DI TAMAN NASIONAL BANTIMURUNG BULUSARAUNG - Muhammad Nurhidayat; Amir Tjoneng; Saida Saida (Percetakan Umi Toaha Makassar, 2019)
MUH.NURHIDAYAT. Level of Community Participation in the Implementation of the Village Conservation Model Program in Bantimurung Bulusaraung National Park (Case Study of Labuaja Village, Cendrana Subdistrict, Maros Regency) (guided by Amir Tjoneng and Hj. Saida)This study aims, 1). Review the implementation process and problems faced in the Conservation Village Model Program around the Bantimurung Bulusaraung National Park area. 2). Assess the level of community participation in the Conservation Village Model Program around the Bantimurung Bulusaraung National Park area. 3). Formulate directions for improving the implementation of the Conservation Village Model Program around the Bantimurung Bulusaraung National Park areaThe research was conducted in the buffer village of the Bantimurung Bulusaraung National Park conservation area, namely Labuaja Village, Cendrana District, Maros Regency, South Sulawesi Province. Field data collection, data processing and analysis as well as thesis preparation took place in February 2016 until May 2016. Data analysis was carried out qualitatively descriptive, namely data analysis based on oral statements arranged in expanded text. The data analyzed are data from interviews, field observations and documentation studies that have been stated in the notes.The results of the study show that, the implementation process consists of 3 (three) stages namely; Planning stages, implementation stages and evaluation stages. The problem faced is that the target community does not understand the Village Conservation Model program. The level of community participation illustrates bahwan, community participation at the planning stage is only 11%, community participation at the implementation stage is only 20.49%, and community participation in the evaluation phase is only 20.49%. The direction for improvement in the implementation of the MDK is the Bantimurung Bulusaraung National Park Office to build collaboration with relevant agencies and Non-Governmental Organizations to encourage the issuance of regional regulations / regulations, improvement of supporting facilities and improving the quality and quantity of assistants to be able to build better business networks and partnerships and to coordinate with forest farmer groups and related agencies.